Philippine politics : possibilities and problems in a localist democracy - White III, Lynn T. (London, United Kingdom : Routledge, 2015)
"Philippine political history, especially in the twentieth century, challenges the image of democratic evolution as serving the people, and does so in ways that reveal inadequately explored aspects of many democracies. In the first decades of the twenty-first century the Philippines has nonetheless shown gradual socioeconomic "progress". This book provides an interpretive overview of Philippine politics, and takes full account of the importance of patriotic Philippine factors in making decisions about future political policies. It analyses whether regional and local politics have more importance than national politics in the Philippines. Discussing cultural traditions of patronism, it also examines how clan feuds localise the state and create strong local policies, and in turn make regional and family-run polities collectively stronger than the central state institution. The book goes on to explore elections in the Philippines, and in particular the ways in which politicians win democratic elections, the institutionalised role of public money in this process, and the role that media plays"-- Provided by publisher.
Local regimes : an introduction -- Malay foundations and colonial semi-modernizations -- Clan feuds localize political violence -- Entrepreneurs as politicians -- Marcos, failed centralization, and land from the tiller -- Law of rule, power of separations -- Populist rituals and elite reformism -- Voting, pork, policy, and media -- Corruption -- PNoy, "Pacquiaos," and the Philippine progress
Includes bibliographical references and index.
Keywords: PHILIPPINES -- POLITICS AND GOVERNMENT